Smart Irrigation System using Arduino Uno - Palanisamy R, Kalyanasundaram,Vidyasagar, George Fernandez S (International Journal of Advanced Science and Technology, 2020)
The basic principle of the project is that the soil moisture sensor obtains the moisture content level of the soil sample. If the moisture content is low then the water pump is automatically turned on which results in flow of water in the soil. The time at which the moisture content is sufficiently high, the water pump is automatically turned off. IoT encompasses many new intelligent concepts for using in the near future such as smart home, smart city, smart transportation, and smart farming. This system is aimed towards the farmers in order to reduce manual labour and increase productivity. In this paper we present water flow monitoring and controlling system which uses a soil moisture sensor to monitor and control the soil moisture content, and water level of the land for monitoring and controlling the amount of water being given to the plant. There is also an automated led lighting system present in the sy